Stand up and fight : participatory Indigenismo, populism, and mobilization in Mexico, 1970-1984 - Muñoz, María L. O. (María Leonor Olin) (The University of Arizona Press, 2016)
"The book examines Indigenous uprisings and agency in Mexico during the 1970s with a focus on the First National Congress of Indigenous Peoples held in 1975"--Provided by publisher.